Pengaruh latihan loncat katak terhadap kemampuan lompat jauh - Yulianto, Rustam; Santoso, Aan Budi; Yulianto, Pipit Fitria (Jurnal Porkes, 2023)
In this study using a pseudo-experimental method, quantitative research type, with a research design using a control group pretest-posttest design. This research is a type of experimental research with a total of 60 subjects of 5th grade elementary school students, then divided into 2 (two) groups by pairing or dividing based on long jump ability in the initial test. Based on the research results that have been obtained by analyzing hypothesis testing data, the value of asymp. Sig (2-tailed) shows less than 0.05, so it can be concluded that there is a difference in the ability of long jump results between the control group and the experimental group so that it can be concluded that there is a significant influence between frog jumping exercises on the long jump ability of elementary school students in Banjarsari Surakarta sub-district. The results of this study indicate that frog jumping training can be an effective method to improve long jumping ability in elementary school students. This has positive implications in the development of basic motor skills, health, and well-being of students.